Challenges and coping strategies of nurses and midwives after maternity leave: A cross‐sectional study in a human resource‐constrained setting in Ghana - Kennedy Dodam Konlan; Joyce Batagidewe Paladaga Pwavra; Mavis Armah‐Mensah; Kennedy Diema Konlan; Rita Aryee; Stephen Narkotey (Nursing Open, 2023)
Abstract Aim This study examined the challenges and coping strategies adopted by nurses and midwives after child birth when they return to work. Design A cross‐sectional design was used. Method Two hundred nurses and midwives with history of maternity leave were recruited from the Korle‐Bu Teaching Hospital to take part in this study. Data were collected using a pre‐tested self‐administered questionnaire. The data were analysed with the aid of Stata 13.0. Results Most of the respondents claimed that they received support from relatives, day care centres and paid house helps while they resumed work. Seventy percent of the respondents indicated that they were given off day when they needed to send their child for postnatal care. Nurses and midwives depend on family members, paid house helps and day care centres to help them cater for their babies. It is recommended that hospitals set‐up day care centres and breastfeeding bays attached to the institutions.